The Bear Cult and Kurgans of the Scythian Elite - V. I. Gulyaev; В. И. Гуляев (Archaeology, Ethnology & Anthropology of Eurasia, 2019)
This study, based on artifacts from high-ranking kurgans of the northern Black Sea region (700–300 BC), addresses the little-studied bear motif in Scythian culture and its relevance for the ancient inhabitants of this region and of the adjacent territories. It is a wide-held view that the image of the brown bear had been borrowed from the Ananyino culture of the Kama. Variation of this motif is described and its chronology is assessed. Two principal iconographic versions are known in Scythian art—the animal is shown either en face, in the so-called sacrifi cial posture, or drinking (in profi le, with a bowed head). Such representations occur most often on gold-plated ritual bowls and ornaments of the horse harness. Both the chronology and the distribution range of these artifacts disagree with the idea that the bear motif was a loan from forest cultures. Rather, it appears to be inherently Scythian, having originated around 700 BC together with other images of the animal style. Apparently, some form of the bear cult was practiced by the Scythian elite. Статья посвящена изучению образа медведя в культуре скифов, его значения для населения Северного Причерноморья и прилегающих территорий. Этот мотив в искусстве скифского населения региона к настоящему времени освещен достаточно слабо. Однако в историографии сложилось устойчивое мнение, что изображения бурого медведя (Ursus arctos) являются заимствованными из ананьинской культуры Прикамья. Материалом для исследования послужил погребальный инвентарь из элитарных захоронений VII–IV вв. до н.э. в Северном Причерноморье. В статье анализируются основные варианты изображений медведя в скифском искусстве, категории предметов, на которых они встречаются, определяются хронологические рамки бытования этого мотива. В результате исследования установлено, что на территории Скифии наиболее распространены два иконографических варианта: медведь в т.н. жертвенной позе (анфас) и пьющий (в профиль с наклоненной головой). Наиболее часто данный мотив встречается на ритуальных чашах с ...